The Roma and their Christian Life in a Pandemic Situation - Ďatelinka, Anton; Akimjaková, Beáta; Mrosková, Lenka; Telezhko, Irina Vladilenovna (Journal of Education Culture and Society, 2022)
Aim. The main goal is to identify not only the religion of the Roma ethnic group, but also their relationship to God, and their experience of faith in the Covid-19 pandemic situation. In the contribution, the authors point to the perception of the personality of the priest as a spiritual shepherd, but also as a figure who leads them to a moral and Christian life. Concept. This scientific study thus points to the classic experience of spiritual life in various selected situations, and identifies the importance of a pandemic situation for a person’s Christian life. Methods. The study deals with several aspects of experiencing the spiritual life of the Roma community, and points out and identifies their thoughts about life during selected social activities. The authors point to important studies that show the connection between the pandemic situation and the issue of faith and religion in the Roma community. Results. The study confirms that the pandemic situation had an adverse effect on experiencing spiritual life in the Roma community, but we can state that Roma carry on their spiritual life despite all the measures in their individual, family community, with the support of other community members. and a priest. Conclusion. The scientific and professional contributions in this study point to the inner experience of spiritual life in the community through individual and family relationships, and the presence of a priest who is supposed to lead the Roma to a spiritual life in accordance with morality.